Parallels and Contextual Implications of Land and Social Justice Motifs in Israel and Ogbomoso Christian Community (2014)
Land and social justice are central to social life in the society of Prophet Micah (Micah), thus their motifs are dominant in the book of Micah of the Old Testament because of the oppressive government in power during the prophets time. Related situations obtained in Ogbomoso between 1978 and 2008, particularly among the Christians, when a number of people and organisations lost their land to the government or other individuals. Previous studies have identified several land and social justice motifs but have not compared these motifs in Micah with traditional Ogbomoso society‘s Christian experience in spite of their similarities. This study, therefore, compared land and social justice motifs in Israel and Ogbomoso Christian community in terms of types and manifestations with a view to establishing their contextual implications. The study was premised on Itumeleng Mosala‘s biblical hermeneutics of liberation, using the historical-critical method. In-depth interviews were conducted with 20 key purposively selected informants comprising 10 community/village heads and 10 opinion leaders across the five local governments in Ogbomoso land. Six Hundred and Fifty copies of a questionnaire were administered to 550 Christian and non-Christian land owners, 50 church leaders, and 50 land agents. Newspaper reports, Church records, land ownership documents and land Use Act of 1978 were also consulted. Data were subjected to exegetical analysis of the Book of Micah, and percentage scores. Three types of land and social justice motifs occurred in both Micah‘s society and Ogbomoso, namely, economic, social and political. Economically, farming constituted the professional hub of Micah‘s society. Consequently, depriving the people access to land (Micah 2: 1-5) had negative economic effects on them. In Ogbomoso, the same effect was exerted through the Land Use Act which affected the financial state of churches. Socially, the deprivation in Micah‘s society led to social discord (Mic. 3:1-4,5:7-15, 7:1-7) as many people were dislocated from their land. A similar situation occurred in Ogbomoso, leading to loss of church-owned schools, itself degenerated into tension between Christians and Muslims; threats to mission investments; and inter/intra family imbroglio. The political leaders of the time of Micah manipulated power to deprive the people of their land (Mic. 2:6-11). This was not manifested in Ogbomoso. One enforcer-based approach used during Micah‘s time was brute force, which received passive, prayer-based responses from the oppressed. The Ogbomoso cases received parallel but sometimes different approaches from the Christians: amicable settlement (25.0%, produced 21.0 % land reclaim), defensive action against attacks and occasional physical assaults (3.0%, produced 3.0% reclaim), litigations (23.0%, produced 12.0% reclaimed), political influence (8.0%, produced 4.0% reclaim) and spiritual invocations (96.0%, led 6.0 % reclaim). Micah‘s society and the Ogbomoso Christian community related to similar economic and social, but different political motifs, converging, with respect to reclaim approaches, only at the spiritual level. This reveals a deflection from the biblical example, which implies that geographic and social contexts rather than strict religious approaches determine effectiveness in land and social justice issues. Thus, achieving success in these issues required a more pragmatic than a biblically consistent approach